PELATIHAN PENDIDIKAN KARAKTER DAN KEPEMIMPINAN PADA SISWA SMK REAL INFORMATIKA BATAM - Sumantika, Arsyad; Ganda Sirait; Darmansah; Yunisa Oktavia (PUAN INDONESIA, 2024)
Real Batam Information Vocational School is one of the schools that has reliable competencies. However, in the educational process, not only knowledge is prioritized, but also related skills and noble character also need to be applied. The aim of implementing this service is to produce a generation, especially students at the Batam Real Information Vocational School, who are not only smart in education, but have a leadership spirit and virtuous character. The expected characteristics include courage, honesty, respect for others and discipline. In this service, the PKM team conducted training for class X students at Real Batam Informatics Vocational School. The form of training is in the form of discussions and sharing regarding how to form a good leadership spirit. Based on the results that have been achieved, after participating in the training held by the PKM team, students are more courageous and confident in their abilities and strengths. Therefore, it is hoped that this training will allow students at these institutions to be able to understand and apply it in their daily lives so that they become young people who are not only intellectually intelligent but also mature in terms of character and leadership in society.